Investigation on effect of ECC coverage condition on seismic behavior of beam-column joint - Zhang, Xinchen (2024)
There is a renewed interest around the world to do fundamental research on novel materials to enhance the overall response of structures under seismic loading. Engineered cementitious composite (ECC) is a special class of concrete with good ductility, which is widely adopted in engineering structures. In this paper, the seismic behavior of beam-column joints incorporated with ECC materials is numerically and experimentally investigated. A database containing available related test results in literature is collected and analyzed to investigate the relations between ECC coverage area and failure characteristics. An interior and an exterior beam-column joint with ECC adopted in the joint region are prepared and tested in this study. The effect of ECC coverage area on the overall joint seismic response is analyzed through a validated finite element model. A modified strength hierarchy analysis is proposed and conducted to consider the application of ECC on the joint. Based on the analytical investigation, the weakest structural element in the joint region is found. The strength hierarchy analysis results have a good correlation with the experimental failure pattern, which shows a potential application as a preliminary analysis to evaluate ECC joint failure mechanisms under seismic loading.